1996
DOI: 10.1093/jmedent/33.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Surrounding Human Settlements and Anopheles albimanus (Diptera: Culicidae) Abundance in Southern Chiapas, Mexico

Abstract: Landscape characteristics that may influence important components of the Anopheles albimanus Wiedemann life cycle, including potential breeding sites, suitable diurnal resting sites, and possible sources of blood meals, were analyzed at 14 villages in a malarious area of southern Mexico. An. albimanus adults were collected weekly in each village using UV-light traps between July 1991 and August 1992. Based on rainfall, the study was divided into 6 seasonal periods. Villages were considered to have high mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Knowing the association between wetlands and mosquitoes is important for mosquito-borne disease as it helps to focus management. Rodriguez et al (1996) found associations between landscape features including elevation and vegetation (mangroves) and malaria vectors in Mexico. Mercer et al (2005) found significant relationships between immature mosquitoes and habitat characteristics such as water quality, in wetlands in Iowa (USA).…”
Section: Mosquito Larval Habitatsmentioning
confidence: 92%
“…Knowing the association between wetlands and mosquitoes is important for mosquito-borne disease as it helps to focus management. Rodriguez et al (1996) found associations between landscape features including elevation and vegetation (mangroves) and malaria vectors in Mexico. Mercer et al (2005) found significant relationships between immature mosquitoes and habitat characteristics such as water quality, in wetlands in Iowa (USA).…”
Section: Mosquito Larval Habitatsmentioning
confidence: 92%
“…These settlements were divided into two groups according to their distance from the larval habitat class. Group 1 was composed of settlements closer than 500 m and group 2 of settlements further than 1500 m. Based on independent measurements, a landing rate of greater than 0´5 mosquitoes per human per minute (during the hours of maximum mosquito activity from 6:30 p.m. to 8:00 p.m.) was used as a threshold for high adult mosquito density ( Rodriguez et al 1996 ). Group 1 was predicted as having adult mosquito densities higher than this threshold and group 2 lower.…”
Section: Disease and Vector Biologymentioning
confidence: 99%
“…Traditionally, regression models have been used to model complex relationships between larval abundance and environmental predictors (e.g. Savage et al 1990, Rejmankova et al 1991, Roberts et al 1991, Beck et al 1994, Rodriguez et al 1996). However, these models do not take into account the location of the samples and often fail to distinguish between different spatial patterns and scales.…”
Section: Introductionmentioning
confidence: 99%